The use of physics pocketbook based on augmented reality on planetary motion to improve students' learning achievement - Nadi Suprapto; Handal Setyo Ibisono; Husni Mubarok (OmniaScience, 2021)
This article is one of the results of the augmented reality (AR)-based pocketbook development on the planetary motion which focuses on student learning achievement. The study used the ADDIE model: "Analysis-Design-Development-Implementation-Evaluation". In the Spring Semester 2020, researchers took these steps in producing an AR-based pocketbook on planetary motion materials. The trial carried out on 30 students at a public high school in Surabaya, Indonesia. Evaluation parameters included the quality of AR-based pocketbook, students' learning achievement, and research outputs. The results showed that: (1) the process of developing an AR-based pocketbook on planetary motion fulfilled the product quality criteria: validity, practicality, and effectiveness; (2) students' learning achievement increase as seen from the results of the pretest-posttest scores with the average Gain score was 0.63 in the moderate category; (3) through the development of an AR-based pocketbook, it resulted in some articles in journals and pocketbook media based on Augmented reality. Planetary motion in physics learning is an abstract concept and requires high reasoning. Therefore, the recommendation of this study is the use of AR as a media for learning in other abstract physics concepts.